Sand Slope Stability Analysis Using the Bishop Simplified Hyrcan 2.0 Method with CaCO3 Reinforcement - Julianto, Baskoro Tri; Ginoga, Sitti Filzha Fitrya (Journal of Civil Engineering and Planning (JCEP), 2025)
Slopes are open land surfaces that form an angle and therefore their stability and safety factors need to be considered. This research aims to analyze the stability of sand slopes using the Bishop Simplified method in Hyrcan 2.0 software with the addition of calcite (CaCO3) as a reinforcement method. Sand slopes have low stability due to low cohesion and lack of interaction between particles, which is exacerbated by the influence of groundwater. The addition of CaCO3 in various concentrations (0%, 10%, and 20%) was applied to improve the shear strength parameters of the sand slope. The simulation model includes six material variations with slope geometric configurations that reflect field conditions. The simulation results showed that the slope with 20% CaCO3 concentration had the highest factor of safety (FOS) of 1.05, compared to 0.73 in the model without reinforcement. Vertically shifting the landslide center point affects the length of the slide plane and the FOS value, where increasing the CaCO3 concentration contributes significantly to improving the slope stability. The relationship between the vertical location of the landslide center and FOS was analyzed using linear regression, which showed a negative relationship between the two. This study concludes that the addition of CaCO3 effectively improves the stability of sand slopes, with FOS approaching safe values although the FOS value in the best model is still categorized as unsafe.